Improving the Teaching of Arabic Through the Effective Use of YouTube - Jumah-Alaso, Salih Muhammad; Onisabi, Abdullahi Shehu (Hijai - Journal on Arabic Language and Literature, 2020)
This study examines ways of improving Arabic's teaching and learning process by applying YouTube video clips as audio-visual aids. Eighteen Arabic students in Kaduna State College of Education and Kwara State University constituted the study sample. A descriptive method with Pre-test and Post-test was conducted. Data were collected through the essay writing, translation, and structure test. The data were analyzed through the descriptive statistics of frequency (f) and percentage (%). The study findings revealed that the subjects performed better and demonstrated linguistic communicative competence in Arabic. Finally, the study recommends that YouTube videos should be integrated into the Arabic teaching-learning process.